2022
DOI: 10.1039/d1nr08305h
|View full text |Cite
|
Sign up to set email alerts
|

High-yield halide-assisted synthesis of metal–organic framework UiO-based nanocarriers

Abstract: The synthesis of nanosized metal–organic frameworks (NMOFs) is requisite for their application as injectable drug delivery systems (DDSs) and other biorelevant purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 63 publications
1
14
0
Order By: Relevance
“…4 ). 33 Our findings confirmed that by using halides, especially chloride, as co-modulators the production of UiO-66-NH 2 and UiO-66 with defined geometries and nanosize is possible.…”
Section: Introductionsupporting
confidence: 85%
See 3 more Smart Citations
“…4 ). 33 Our findings confirmed that by using halides, especially chloride, as co-modulators the production of UiO-66-NH 2 and UiO-66 with defined geometries and nanosize is possible.…”
Section: Introductionsupporting
confidence: 85%
“…17–20% w/w for all the synthesized NPs. 33 These values show the efficiency of this method to encapsulate the cargo in a post-synthetic method.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…16,[24][25][26][27] The unique structure and performance advantages make it a potential material for a broad range of applications. [28][29][30][31] To obtain Zr-MOF nanoparticles (NPs), many techniques have been used, including microwave, 32 microemulsion strategy, 33 modulated synthesis, [34][35][36] and mechanochemical synthesis. 37 However, these methods often require complex control conditions, and have problems such as long reaction time, low yield, and large size distribution.…”
Section: Introductionmentioning
confidence: 99%